Adjuvant chemotherapy can benefit the survival of stage I lung adenocarcinoma patients with tumour spread through air spaces after resection: Propensity-score matched analysis - Xie, Shaonan; Liu, Qingyi; Han, Yaqing; Wang, Shize; Deng, Huiyan; Liu, Guangjie (Frontiers in Oncology, 2022)
Background: It is still unclear whether stage I lung adenocarcinoma patients with tumour spread through air spaces (STAS) can benefit from postoperative adjuvant chemotherapy (ACT) after lobectomy. This study investigated the effect of ACT on the postoperative survival of patients with stage I (STAS+) lung adenocar-cinoma. Methods: We retrospectively analysed the clinical data of stage I (STAS+) invasive lung adenocar-cinoma patients who underwent lobectomy in the Department of Thoracic Surgery of our hospital from Jan-uary 1, 2013 to January 1, 2016. Propensity score matching (PSM) was performed to group patients to in-vestigate whether ACT could lead to better prognosis of patients. Results: A total of 593 patients with stage I (STAS+) lung adenocarcinoma were enrolled. The study after PSM included 406 patients. Kaplan–Meier survival analysis showed the experimental group had a better 3-year recurrence-free survival (RFS) rate (p = 0.037) and the 5-year RFS rate (p = 0.022) than the control group. It also had higher 5-year overall survival (p = 0.017). The multivariate analysis by Cox proportional hazard regression model showed that stage I STAS+ lung adenocarcinoma patients with lymphatic vessel invasion (HR: 1.711, 95% CI: 1.052-2.784; p = 0.045), vascular invasion (HR: 5.014, 95% CI: 3.154-7.969; p < 0.001), and visceral pleural invasion (HR: 2.086, 95% CI: 1.162-3.743; p = 0.014), and without ACT (HR: 1.675, 95% CI: 1.043-2.689; p = 0.033) had a significant survival disadvantage. Conclusion: ACT can boost the postoperative survival of patients with stage I (STAS+) lung adenocarcinoma.